Sistem Pengelolaan Persediaan Barang Dagang Pada UMKM - Ni Luh De Erik Trisnawati; Ketut Suryaningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research aims to understand the inventory management system for retail goods at UMKM Sari Rasa, which operates in the wholesale and retail sector of snack nuts, particularly kapri nuts. This study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The research results explain that the global recording system at UMKM Sari Rasa indicates that the business has not implemented a detailed inventory system, leading to discrepancies which ultimately risk inconsistencies between the recorded data and physical condition of the goods in the warehouse. The researcher applies a perpetual inventory recording system using the FIFO (First In First Out) method, which can record inventory flows in real-time, prioritizing older stock for sale, and minimizing damage to goods due to ineffective inventory management. Researchers also compiled SOPs and flowcharts for storing goods as operational guidelines for the warehouse section.